Fibrin and Fibrinogen Proteolysis Products: Comparison between Gel Filtration and SDS Polyacrylamide Electrophoresis Analysis - Alkjaersig, Norma; Davies, Andrew; Fletcher, Anthony (Thrombosis and Haemostasis, 1977)
The proteolysis of purified human fibrinogen, stabilized and non-stabilized fibrin by plasmin were investigated by gel filtration analysis and SDS polyacrylamide electrophoresis of the reaction products. Plasmin proteolysis of fibrinogen followed the sequential steps previously reported and the two analytical methods yielded concordant results. Large molecular weight proteolysis products, of substantially greater molecular weight than native fibrinogen, were identified by gel filtration analysis following dissolution of stabilized and non-stabilized fibrin clots; with further incubation with plasmin, these proteolysis products gradually diminished in size. On the other hand, SDS polyacrylamide electrophoresis of these fibrin digests demonstrated that while non-stabilized fibrin yielded breakdown products similar in size to those obtained after proteolysis of fibrinogen, stabilized fibrin digests showed moieties of greater molecular size estimated to be of molecular weight 400,000 to 800,000. The final breakdown products of stabilized fibrin differed from those of fibrinogen and nonstabilized fibrin in that fragment D was present in the “double D” cross-linked form.